LANSIA SEHAT, LANSIA AKTIF DAN BERSAMA ATASI HIPERTENSI - Adyani, Sang Ayu Made; Tobing, Duma Lumban; Anggraini, Nourmayansa Vidya; Marwah, Safa; Salsabila, Talita Alifa; Wahyudi, Chandra Tri (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Elderly people experience various declines in body function which can cause various health problems. The problem that is often encountered is hypertension. If hypertension in the elderly is not treated, it will cause various complications and can reduce the quality of life of the elderly. The knowledge and skills of elderly people in managing hypertension through health education and elderly exercise. The exercise carried out is low impact aerobic exercise taking into account the abilities of the elderly. Exercises are done in a sitting position. Elderly people are expected to be able to practice exercise and maintain a healthy lifestyle so that theit blood pressure is controlled.